Peralihan Hak Atas Tanah Dengan Perjanjian Jual Beli Menurut Hukum Pertanahan Indonesia - Ayu Larasati; Raffles Raffles (Universitas Jambi, Fakultas Hukum, 2020)
This article talks about the legal arrangements regarding the transfer of land rights through the sale and purchase of land for land that has not been registered; and legal consequences of the transfer of land rights because it is not registered at the Land Office in terms of Government Regulation concerning Land Registration. The research method used is the normative legal research method and the approach used is the statutory approach and the conceptual approach ). The results of the study show that, first, the legal arrangements regarding the transfer of land rights through the sale and purchase of land for land that has not been registered, the transfer of rights to land due to the sale and purchase of land that has not been registered or in other words uncertified land rights in the provisions of Government Regulation concerning Land Registration can be sold / transferred ownership rights with the main requirement that the seller is able to show proof of ownership of land such as a previous sale and purchase letter (seal letter), kekitir / petok / girik, statement of the village head / local official, which explains the truth about ownership of the land owner. Second, the legal consequences of the transfer of land rights because they are not registered at the Land Office in terms of Government Regulation concerning Land Registration are legal according to the law if the transfer of land rights due to the sale and purchase of land that has not been registered already meets the material purchase requirements, namely